2018
DOI: 10.1007/s00216-018-1183-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of human C24 bile acids metabolome in serum and urine based on enzyme digestion of conjugated bile acids and LC-MS determination of unconjugated bile acids

Abstract: Host-gut microbiota metabolic interactions are closely associated with health and disease. A manifestation of such co-metabolism is the vast structural diversity of bile acids (BAs) involving both oxidative stereochemistry and conjugation. Herein, we describe the development and validation of a LC-MS-based method for the analysis of human C24 BA metabolome in serum and urine. The method has high throughput covering the discrimination of oxidative stereochemistry of unconjugated species in a 15-min analytical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 51 publications
1
49
0
Order By: Relevance
“…As shown in Fig. 1, A-C, we found five unknown tri-hydroxyl BA species (TBA05, TBA09, TBA10, TBA13 and TBA18) in the Tertiary Bile Acids Metabolism 285 at ASPET Journals on July 10, 2020 dmd.aspetjournals.org post-prandial urine and serum of 13 healthy volunteers collected at UNC-CH Hospitals (Zhu et al, 2018). Enzyme digestion techniques demonstrated that they were extensively conjugated, thus, explaining their "invisibility" to those direct analysis techniques without consideration of BA conjugation.…”
Section: Resultsmentioning
confidence: 67%
See 4 more Smart Citations
“…As shown in Fig. 1, A-C, we found five unknown tri-hydroxyl BA species (TBA05, TBA09, TBA10, TBA13 and TBA18) in the Tertiary Bile Acids Metabolism 285 at ASPET Journals on July 10, 2020 dmd.aspetjournals.org post-prandial urine and serum of 13 healthy volunteers collected at UNC-CH Hospitals (Zhu et al, 2018). Enzyme digestion techniques demonstrated that they were extensively conjugated, thus, explaining their "invisibility" to those direct analysis techniques without consideration of BA conjugation.…”
Section: Resultsmentioning
confidence: 67%
“…Enzyme digestion techniques demonstrated that they were extensively conjugated, thus, explaining their "invisibility" to those direct analysis techniques without consideration of BA conjugation. The Quad time-of flight MS/MS spectra captured in the digested urine samples showed that they had fragment ions possibly associated with 12-hydroxylation on the skeleton (Lan et al, 2016;Zhu et al, 2018). They were therefore supposed to be structurally associated with DCA and CA, the two major BAs with 12-hydroxylation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations